2007
DOI: 10.1093/ps/86.5.959
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Season and Market Class of Broiler Chickens on Breast Meat Quality Traits

Abstract: The influence of the season and market class of broiler chickens on breast meat quality traits was determined on a total of 18 flocks reared and processed under commercial conditions. According to the Italian poultry production system the following classes of birds were considered: light size (1.2 kg of carcass weight; n = 90) and medium size (1.8 kg of carcass weight; n = 90), represented by females slaughtered at 40 and 52 d old, respectively, whereas heavy size were 57-d-old male broilers (2.4 kg of carcass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
41
4
13

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 24 publications
9
41
4
13
Order By: Relevance
“…This difference in color might represent an important factor affecting consumers' preferences, considering that Bianchi et al (2007) reported that consumers preferred different colors, depending on their place of residence. Table 3 provides the major fatty acids of the KNC and CB breast and thigh muscles.…”
Section: Ph Whc and Colormentioning
confidence: 99%
“…This difference in color might represent an important factor affecting consumers' preferences, considering that Bianchi et al (2007) reported that consumers preferred different colors, depending on their place of residence. Table 3 provides the major fatty acids of the KNC and CB breast and thigh muscles.…”
Section: Ph Whc and Colormentioning
confidence: 99%
“…High muscle pH is generally associated with darker meat (Fletcher, 1999). The color difference is an important factor influencing consumer preferences, although these preferences depend on the place of residence (Bianchi et al, 2007). The characteristic difference in color among NKNC, SKNC, and CB may influence the consumer choices.…”
mentioning
confidence: 99%
“…Bianchi et al (2007) reported a similar trend for chicken; specifically, they found higher drip loss in summer than in winter. The decrease of water-holding capacity during summer could be attributed to the high muscle temperature recorded during this season.…”
Section: Effect Of Slaughter Season On the Different Parametersmentioning
confidence: 55%
“…Extensive studies have been reported about the effect of slaughter season on meat quality in different species such as rabbit (María et al, 2006), chicken (Bianchi et al, 2007), goat (Kadim et al, 2008b), beef (Węglarz, 2010), lamb (Chulayo and Muchenje, 2013;D'Alessandro et al, 2013;Sanchez-Sanchez et al, 2013) and pig (Correa et al, 2014). However, these aspects were not common for camels.…”
Section: Effect Of Slaughter Season On Postmortem Metabolic Charactermentioning
confidence: 99%